On the elastoplastic stability of a plate under shear forces, taking into account its real bending form - Bich, Dao Huy (Vietnam Journal of Mechanics, 2001)
Using the theory of elastoplastic processes and the modified elastic solution method we investigate the stability outside elastic limit problem of a plate under shear forces, taking into account its real bending form after the loss of stability. An expression for determining the critical force is obtained and numerical calculations with various ratio of thickness have been fulfilled, from the results one can see the convergence of the modified elastic solution method.